The importance of personal hygiene - Pfuetze, Anna Cristine (My University, 1899)
Introduction: The question of personal hygiene has, in late years, become one of very great importance, especially among the more cultured people. We have passed the age when people can be “dragooned into clean lines”, or be “made virtuous by police regulations”. The way to spread sanitary science is to educate the masses. It was a part of the Jewish Code to care properly for the body. The Greeks also took good care of their bodies. Yet they knew little of the causes of disease, and the same is true of the Romans. Today, the great problem of health and disease is to know the causes of disease, so as to promote the former and prevent the latter. In the Middle Ages, our forefathers lived in very unsanitary conditions. They very seldom changed their clothing; their diet was course; they used much ale; and their houses were very filthy.
Citation: Pfuetze, Anna Cristine. The importance of personal hygiene. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Promoters of Health; Fresh Air; Cleanliness; Care in handling Wool Hides; Theses; Manuscripts (documents)